Evidence for photic zone euxinia through the end-Permian mass extinction in the Panthalassic Ocean (Peace River Basin, Western Canada) - Hays, Lindsay E.; Beatty, Tyler; Henderson, Charles M.; Love, Gordon D.; Summons, Roger E. (Palaeoworld, 2007)
A combination of sequence stratigraphic and conodont biostratigraphic analyses of sediment cores from five petroleum exploration wells, together with reference to nearby outcrops, has allowed us to construct a composite geological section through the Permian-Triassic transition in the Peace River Basin of Western Canada. The cores contain significant contents of organic matter comprising kerogen and bitumen of low to moderate thermal maturity. Extraction and analysis of the bitumens has revealed patterns of biomarker hydrocarbons consistent with marine deposition and photic zone euxinia. In particular isorenieratane and aryl isoprenoids, derived from the carotenoid pigments of green sulfur bacteria (Chlorobiaceae), are abundant and pervasive throughout the section and indicate that hydrogen sulfide must have been present in the photic zone for significant periods of time. These findings mirror the geochemical results obtained for other Permian-Triassic boundary sections of the Tethys realm (e.g. Western Australia, East Greenland and South China) and suggest that euxinic conditions prevailed widely, though perhaps periodically, and that hydrogen sulfide toxicity could have been an important factor in the extinction of marine invertebrates.